Policy Strategy for Value-Added Tax Imposition on Social Commerce Transactions - Tambunan, Maria R.U.D.; Afina, Siti Zaila Noor (UI Scholars Hub, 2025)
The burgeoning e-commerce sector offers a promising avenue for tax revenue. However, aligning its regulatory measures with continuous advancements presents challenges. The government has recently issued a regulation that separates commerce and social media functions within social commerce platforms. This study analyzes the determinants to consider in formulating a value-added tax (VAT) policy on economic activities conducted through social commerce platforms and the effective VAT collection strategy. A qualitative descriptive approach was employed, with in-depth interviews and a literature review as data collection techniques. The key finding highlights the importance of efficiently managing data for businesses operating in social commerce platforms, streamlining tax costs, ensuring equitable tax regulation across various platforms, and enhancing the current manual monitoring system by integrating data from Statistics Indonesia. To establish effective tax collection, an integrated system capturing social commerce transactions is pivotal. Furthermore, applicable VAT regulations lack clear guidelines for social commerce, necessitating their formulation. Despite some administrative provisions covering marketplaces, the scope should expand to include social commerce. The Social Network Analysis application by the tax authority, intended for data provision and monitoring, remains unintegrated and requires immediate improvement.